Educational ideas of Confucius. - King-Mao Tong 1925- (Quezon City s.n., 1966)
This study is confined to the educational ideas of Confucius. The study of Confucian philosophy is considered necessary for the purpose of saving Chinese culture from being ruined by the Marxism followers. The recommendations and implications of which are the emphases of this study.
Thesis (M. Ed.) -- University of the Philippines.
Keywords: Confucius and Confucianism